Effects of intercropping teak with Alpinia katsumadai Hayata and Amomum longiligulare T.L. Wu on rhizosphere soil nutrients and bacterial community diversity, structure, and network - Xianbang, Wang; Mingping, Lin; Kunliang, Li; Qiang, Han; Dongkang, Pan; Haibin, Ma; Guihua, Huang (Frontiers in Microbiology, 2024)
Teak is a precious hardwood species in tropical and subtropical regions with a long growth cycle and slow economic returns. Intercropping medicinal plants is an effective method for obtaining early returns during the growth period of teak. However, currently, we lack sufficient knowledge about the impact of intercropping on the soil microenvironment, especially on rhizosphere soil bacterial communities. We selected two medicinal plants Alpinia katsumadai Hayata and Amomum longiligulare T.L. Wu, for an intercropping experiment with teak, and the non-intercropping teak forest area was used for comparison. By collecting soil rhizosphere samples and conducting 16S rDNA sequencing and property analysis, we aimed to investigate the influence of teak intercropping on soil microbial communities. The results showed that intercropping significantly improved soil nutrients contents, such as soil organic matter, soil total potassium and soil available nitrogen, and significantly altered bacterial community structure. Co-occurrence network analysis revealed that intercropping tightened the connections of the soil bacterial network and increased its complexity (by increasing the number of nodes and the proportion of positive edges). Teak intercropping with Amomum longiligulare T.L.Wu resulted in tighter network connections than teak intercropping with Alpinia katsumadai Hayata. Changes in the soil bacterial community structure may related to environmental factors such as total potassium content and pH. These results demonstrated that the introduction of medicinal plants exerts a significant impact on the soil bacterial community of teak, fostering the enrichment of specific bacterial taxa (such as Firmicutes and Methylomirabilota), and makes the rhizosphere bacterial network denser and more complex. This study provides valuable insights for the management of teak plantations